2016
DOI: 10.1194/jlr.m067165
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect vitamin A supplementation strategies result in different plasma and tissue retinol kinetics in neonatal rats

Abstract: Many questions remain regarding vitamin A (VA) supplementation of infants. Herein we compared direct oral VA supplementation of the neonate and indirect treatment through maternal dietary VA (M-VA) treatment on VA status and kinetics in neonatal rats. Treatments included direct VA combined with retinoic acid (RA) [D-VARA; VA (6 mg/kg) + 10% RA, given orally to neonates on postnatal day (P)2 and P3] and indirect VA supplementation through increased M-VA, compared with each other and oil-treated neonates. [3H]re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…First, as expected from previous findings [30,37], regardless of being added to the NFD or the HFD, maternal VA supplementation during lactation significantly increased the VA concentration in Figure 4. Ratio of total retinol mass in the liver to in serum (A), and that in white adipose tissue to in serum (B).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…First, as expected from previous findings [30,37], regardless of being added to the NFD or the HFD, maternal VA supplementation during lactation significantly increased the VA concentration in Figure 4. Ratio of total retinol mass in the liver to in serum (A), and that in white adipose tissue to in serum (B).…”
Section: Discussionsupporting
confidence: 89%
“…First, as expected from previous findings [30,37], regardless of being added to the NFD or the HFD, maternal VA supplementation during lactation significantly increased the VA concentration in maternal milk and raised the VA status of neonatal rats as evidenced by improved serum and liver VA concentrations. The 14-day-old pups in non-VA-supplemented groups showed a marginal to normal serum VA status and a deficient to marginal liver VA status.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Therefore, the objective of this exploratory study was to assess, in neonatal and weanling rat offspring from mothers consuming an HFD, how VA supplementation will modulate their BW, adiposity, and obesity-associated metabolic conditions, including redox and inflammatory status, glucose, lipid profile, and adipokines. VA supplementation through enriching the maternal diet was chosen as the supplementation route for neonates, because it was shown to have a significantly greater sustained effect on improving neonatal VA status than VA treatment directly given to neonates ( 26 ). Considering its potential teratogenic effect, maternal VA supplementation was administered during lactation, but not the gestational period.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, new experimental studies in animal models have resulted in a deeper understanding of retinol metabolism in the neonate, for example by showing that a much larger portion of chylomicron vitamin A is taken up by extrahepatic tissues in the neonate compared with the adult, and that supplementation with vitamin A alters turnover rates significantly ( 11 ). Such studies have also shown that storage tissues such as the liver and lung do not hold on to the vitamin A provided in a high-dose supplement for more than a few days, whereas in contrast, vitamin A provided to the mother for transfer in milk results in a more gradual but longer-sustained increase in tissue vitamin A, and thus accumulation over a longer period of time ( 12 ). The results also suggest that neonates grow well and are able to maintain a normal concentration of plasma retinol in the face of much lower hepatic reserves of vitamin A, as compared with adult animals ( 11 ).…”
Section: Looking Forward: What Has Changed and Why Might It Be Time mentioning
confidence: 99%